2014
DOI: 10.3238/arztebl.2014.0367
|View full text |Cite
|
Sign up to set email alerts
|

Triggers and Treatment of Anaphylaxis

Abstract: Wasp and bee venom, legumes, animal proteins, and analgesic drugs were the commonest triggers of anaphylaxis. Their relative frequency was age-dependent. Epinephrine was given too rarely, as it is recommended in the guidelines for all cases of grade 2 and above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 27 publications
7
53
1
3
Order By: Relevance
“…The release of vasoactive mediators into the circulation can lead to vascular collapse and anaphylactic shock. 72 Supplementary Table 1 summarizes the clinical manifestations of food allergies, the organ systems affected by IgE-mediated mast cell and basophil degranulation, and the clinical aspects of gastrointestinal food allergy. 3,6 …”
Section: Pathogenesis and Manifestations Of Food Allergymentioning
confidence: 99%
“…The release of vasoactive mediators into the circulation can lead to vascular collapse and anaphylactic shock. 72 Supplementary Table 1 summarizes the clinical manifestations of food allergies, the organ systems affected by IgE-mediated mast cell and basophil degranulation, and the clinical aspects of gastrointestinal food allergy. 3,6 …”
Section: Pathogenesis and Manifestations Of Food Allergymentioning
confidence: 99%
“…In contrast, potentially fatal severe systemic reactions often involve vascular and respiratory systems and can cause multiorgan failure [1]. Hymenoptera stings are among the most frequent causes of severe anaphylaxis in adults in Europe [2] and account for approximately 20% of the anaphylaxis-related fatalities worldwide [3]. The prevalence of systemic reactions ranges from 0.3-7.5% in European population [4] and from 0.5-3.3% in the United States [5], while in Latin America, Hymenoptera stings elicit about 15% of the severe allergic reactions annually reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies have reported a prevalence of bee and wasp induced anaphylaxis ranging from 0.3 to 8.9% in adults and from 0.15 to 0.8% in children [2, 3]. Several studies have reported bee and wasp stings to be the most common trigger of anaphylactic reactions in adults [4, 5]. The incidence of fatalities due to bee and wasp induced anaphylactic reactions ranges from 0.3 to 0.48 cases per one million inhabitants per year, representing around 20% of fatal anaphylaxis from any cause [2, 3].…”
Section: Introductionmentioning
confidence: 99%